The Improvement of Quality Control Checklist in Bogie Assembly for Kuala Lumpur Additional Vehicle (KLAV 27) Project - Nurul Farah Nabilah binti Mohamad Kadri; Mustapha Kamil bin Omran; Mohd Noor Fathullah bin Mohd Noordin (Progress in Engineering Application and Technology, 2023)
The absence of quality checklist at every station of the bogie assembly might cause some errors that could even lead to fatality. The purpose of this paper is to propose an improved quality checklist for bogie assembly for every station and focusing on the bogie assembly process for Kuala Lumpur Additional Vehicle 27 (KLAV 27) project. The method that is used in this study is Six Sigma’s DMAIC to propose an improved quality control checklist at each station of bogie. At the end of the study, there are six improved quality control checklists for each station of bogie assembly was produced which overcame the problems that occurred such as delayed in bogie assembly process. Therefore, the bogie assembly process is more efficient and produces quality products.